Radical Ambivalence: Engaging Poststructurally with Performance, (Re)Envisioning the Political - Wiebe, Brandy (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
This paper uses poststructural theories, in particular Judith Butler's work, to analyze the performances and interviews of Vancouver-based performers Heather Robertson and Nikki Prime-French and explores how feminist political intervention need not always be directly intentional and organized to be effective.